Public relations and micropolitics: a comparative study of their processes and programs - Simões, Roberto Porto (2008)
This article contains a comparative study between the processes and programs of Public Relations and micropolitics, deepening the theory of the management of the political organizational function to explain the activity of Public Relations. It discusses the political design and power relationship. It reduces the angle of macropolitics to micropolitics. Integrates the concepts of micropolitics existing in the areas of education and political science. Explain that organization is, par excellence, a political arena. It carries out the comparative study demonstrating the coincidence between the processes and programs of micropolitics and Public Relations. Finally, it focuses on communication as an instrument of the exercise of power, being this the essence and the communication, the appearance.